2019
DOI: 10.1093/cdn/nzz012
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Healthy Eating in Adults: An Evaluation of Pleasure-Oriented versus Health-Oriented Messages

Abstract: Background Existing initiatives to promote healthy eating remain largely ineffective as individuals struggle to adhere to dietary recommendations. Therefore, challenging the strategies currently used is of significant importance. Recent studies have indicated the potential of an approach oriented towards eating pleasure to promote the consumption of healthy foods. Objectives The aim of this study was to compare perceptions and the potential effect of pleasure-oriented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
12
0
2
Order By: Relevance
“…In the literature, the cross-cultural comparison has been described as comparisons by which established practices and behaviors from two or more different countries or societies are contrasted and reflected against the respective countries' cultural particularities [26]. Previous cross-cultural studies have suggested that populations that prioritize pleasure over health, e.g., southern European populations, demonstrate healthier eating behaviors [27]. One might expect that the Mediterranean diet and the convivial and social value attributed to eating [20] may play an important role in the Italian sample and be less associated with ON than in the Polish sample.…”
Section: Cross-cultural Comparison Of Orthorexia Nervosamentioning
confidence: 99%
“…In the literature, the cross-cultural comparison has been described as comparisons by which established practices and behaviors from two or more different countries or societies are contrasted and reflected against the respective countries' cultural particularities [26]. Previous cross-cultural studies have suggested that populations that prioritize pleasure over health, e.g., southern European populations, demonstrate healthier eating behaviors [27]. One might expect that the Mediterranean diet and the convivial and social value attributed to eating [20] may play an important role in the Italian sample and be less associated with ON than in the Polish sample.…”
Section: Cross-cultural Comparison Of Orthorexia Nervosamentioning
confidence: 99%
“…In addition, research on food choice has found that Southern European populations give greater importance to sociability and cooking and enjoying food with others [42]. Cross-cultural studies have suggested that populations that prioritize pleasure over health demonstrate healthier eating behaviours [42,43]. One might expect that the Mediterranean diet together with convivial and social value attributed to eating [40] may play an important role in the Spanish sample.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the collected data, we could conclude that messages focused on the pleasure of plant-based meals could result in their higher acceptance level. Despite the limited evidence on the effectiveness of such a framing shown by Vaillancourt C., et al [83], this strategy still seems promising. The question who should ultimately be responsible for conducting meat reduction interventions remains relevant.…”
Section: Discussionmentioning
confidence: 99%